Physical and physiological factors associated with success in the triathlon - Sleivert, G. G.; Rowlands, D. S. (Sports Medicine, 1996)
The physiological demands of sequential exercise in swimming, cycling and running are unique and require the triathlete to develop physical and physiological characteristics that are a blend of those seen in endurance swimming, cycling and running specialists. Elite triathletes are generally tall, of average to light weight and have low levels of body fat, a physique which provides the advantages of large leverage and an optimal power to surface area or weight ratio. Triathletes have high maximum oxygen uptake (VO2max) values, but VO2max may be on average marginally lower than values previously observed in endurance specialists. Although VO2max is a predictor of performance in triathletes of mixed abilities, it cannot be used to predict performance within homogenous groups of elite performers. Nevertheless, elite triathletes have significantly higher VO2max values than sub-elite triathletes and high VO2max levels are required for success in triathlons. The ability of the triathlete to exercise at a lower percentage of VO2max for a given submaximal workload may be especially important to triathlon success. This is influenced not only by VO2max itself, but also by anaerobic threshold and economy of movement. Anaerobic threshold, as indicated by either ventilatory threshold or lactate threshold, improves with triathlon training and when measured in the appropriate exercise mode has been related to swim, cycle and run performance in the triathlon. Economy of movement in swimming, cycling and running is also related to triathlon performance, and swimming economy in particular appears to be an area where triathletes could make large improvements. Future research should utilise experimental methodologies to investigate triathlon physiology, in particular, the influence of sequential exercise in different exercise modes on physiological function and examine the influence of different training interventions on triathlon physiology and performance.